Radiological evidence of femoroacetabular impingement in asymptomatic athletes. Issue 4 (27th March 2011) - Abellàn, J; Esparza, F; Blanco, A; Martínez, M; Merino, G Ruiz; Lisón, A
Abstract : Background: Femoroacetabular impingement (FAI) has been stated as one of the main causes of early osteoarthritis in the hip. This is particularly important in young athletes. However, there are no data available about the prevalence of radiological signs of FAI in the asymptomatic population. These data would improve the evaluation of athletes with groin pain to prevent further injuries. Objective: The aim of this study is to show the prevalence of radiological signs of FAI in non-symptomatic athletes. Design: Descriptive study. Setting: Soccer and basketball players enrolled in elite division leagues. Participants: Players were selected from the teams of the Federation of Soccer and Basketball of Murcia. Interventions: Participants were clinical and radiologically evaluated. Clinical exam included: range of motion, and anterior and posterior hip impingement tests. Radiological exam included both anteroposterior radiographs of the pelvis and axial (frog-leg) views of both hips. Main outcome: Radiographs were assessed to detect signs of FAI (both cam and pincer type). These signs were: pistol grip deformity (PG), coxa vara, alfa angle higher than 50°, anterior offset ratio (OR) lower than 0.18, coxa profunda/Protasio acetabuli (CP/PA), acetabular index lower o equal to 0°, cross-over sign (CO), and posterior wall sign (PW). Results: 80 athletes were evaluated (mean (SD) age 24.43 (3.21)). PG was present in the 28.8%, alfa was higher than 50° in the 43.8%, CP/PA was detected in the 41.25%, CO was seen in the 25%, and PW in the 8.8%. Clinical signs of FAI, that is, groin pain with provocative test, were positive in the 13.8% of the patients. Conclusion: Radiological evaluation shows a high prevalence of signs of FAI in athletic population. However, clinical signs are only present in a few of them.